2018
DOI: 10.21608/smj.2018.31720
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Endoscopic Management of Multiloculated Hydrocephalus

Abstract: The aim of this study is to evaluate the role of endoscopy in management of multiloculated hydrocephalus. PATIENTS AND METHODS: We reviewed 30 consecutive patients during the period from January 2012 to December 2015 with multiloculated hydrocephalus who underwent neuroendoscopic approach for treatment, in Sohag university Hospital. The patients' clinical outcomes, and complications were reported. RESULTS: There were 30patients (12male18 female).endoscopic septum pellucidum fenestration was done in 9 cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The low rate and severity of complications observed in our patients are in line with the previous studies which concluded that complications following endoscopic approach were usually minor and were mostly treated conservatively. [ 8 , 9 , 12 , 13 , 17 , 25 , 29 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low rate and severity of complications observed in our patients are in line with the previous studies which concluded that complications following endoscopic approach were usually minor and were mostly treated conservatively. [ 8 , 9 , 12 , 13 , 17 , 25 , 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Fadl et al . [ 13 ] stated that none of their 30 MLH patients who underwent endoscopic management suffered from intra- or postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation